2018
DOI: 10.4314/jae.v22i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effect of climate change on forest dependent livelihoods in Oyo State, Nigeria

Abstract: The study investigated the perceived effect of climate change on forest dependent rural livelihoods in Oyo State, Nigeria with the view of identifying possible adaptation strategies. A total of 208 respondents were randomly sampled from Olokemeji and Onigambari forest reserves in Oluyole and Ibarapa East Local Government Area (LGA), respectively. Data collected were analyzed using frequency distribution, percentages Chi square and PPMC. Result shows that major livelihood activities were farming (100.0%) and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Table 1 reveals that the majority of the respondents agreed that heat stress (mean (M=4.10) constituted the highest threat to human health in the study area, this could be a result of unpredictable increases in the temperature beyond what can be tolerated thereby causing stress among the respondents. This finding is congruent with the finding of Akinbile et al (2018) that an increase in temperature as a result of climate change is a major threat perceived by farmers as effects of climate change Secondly, a decrease in productivity of the farmers as a result of climate change (M= 4.06) was also considered as one of the highest impacts. The farmers believe that unfavourable climate change has resulted in crop failure and the death of the animal on their farm.…”
Section: Effects Of Climate Change On Human Healthsupporting
confidence: 89%
See 1 more Smart Citation
“…Table 1 reveals that the majority of the respondents agreed that heat stress (mean (M=4.10) constituted the highest threat to human health in the study area, this could be a result of unpredictable increases in the temperature beyond what can be tolerated thereby causing stress among the respondents. This finding is congruent with the finding of Akinbile et al (2018) that an increase in temperature as a result of climate change is a major threat perceived by farmers as effects of climate change Secondly, a decrease in productivity of the farmers as a result of climate change (M= 4.06) was also considered as one of the highest impacts. The farmers believe that unfavourable climate change has resulted in crop failure and the death of the animal on their farm.…”
Section: Effects Of Climate Change On Human Healthsupporting
confidence: 89%
“…This finding corroborates the finding of Turkiye (2023) reported that climate change has claimed up to 36,698 deaths from ambient air pollution in Türkiye in 2016 which was a result of climate change impact. In summary, this result on the effects of climate change on health is in line with the result of Akinbile et al (2018) who discovered that the impacts of climate on the livelihood of the forest dwellers in Oyo state, Nigeria include a reduction in food production and high vulnerability to diseases and pest. This finding calls for sensitization by extension agents and health workers on how the rural households in that area can cope with climate change to reduce the effect of damages caused and the mortality rate among rural dwellers.…”
Section: Effects Of Climate Change On Human Healthsupporting
confidence: 84%
“…In this context, the amount of moisture remaining in the dewatered solids plays a crucial role in determining the expenses associated with disposal, while the quality of the centrate (liquid fraction) influences the level of pollution reintroduced into the treatment facility. A centrifuge, a device commonly employed for solid-liquid separation, eliminates solid particles from wastewater [42].…”
Section: Sludge Treatmentmentioning
confidence: 99%
“…Changes in precipitation patterns increase the likelihood of short-run crop failure and long-run production declines. Also, Akinbile [3] noted that estimate of the effects to climate change on crop yields are predominantly negative for the tropics. In support of Adebisi et al [2], Mark et al [4] highlighted some of the direct effects of climate change on agricultural system as seasonal changes in rainfall and temperature, which could impact agro-climatic conditions, altering growing seasons, planting and harvesting calendars, water availability, pest, weed, disease populations, alteration in evapo-transpiration, photosynthesis, business production, alteration in land suitability for agricultural production.…”
Section: Introductionmentioning
confidence: 99%